Towards Peace in Jammu, Kashmir and Ladakh - Majid Siraj; SIRAJ (Majid) (New Delhi Manas Publications, 2003)
The Book Is A Unique Approach Not Only To Chronicle The Singularities Of The Complex Discord Ravaging This Beautiful Part Of The Sub-Continent But To Highlight The Ways Of Getting Out Of The Morass. Peace Making Is A Challenge But By Exploiting The Momentum In The Right Direction, A Ripple Effect Takes Over And The Goal Of An Ultimate Solution Can Be Achieved. Pakistan'S Sponsored Terrorism Is Prelude To Disorder & Responsible For Inordinate Suffering. We Witness The Colossal Pain People In This Region Have Been Enduring For Many Years. Political Thinkers Have Come Out With Thought Provoking Views Which Conform With The Cause And Effect Basis Of The Dispute. The Book Invokes Strands Of Higher Politics And Philosophy. It Gives A Different And Unique Thought For The Politics In South Asia.